Answer:
negative
Step-by-step explanation:
Suppose we have positive integer x and negative integer -y.
Subtracting x from -y gives:
-y - x
Clearly, if -y is negative and we're subtracting even more (x) from it, the answer will still be negative.
So, the sign is negative.
~ an aesthetics lover
Answer:
negative
Step-by-step explanation:
Suppose we have positive integer x and negative integer -y.
Subtracting x from -y gives:
-y - x
Clearly, if -y is negative and we're subtracting even more (x) from it, the answer will still be negative.
So, the sign is negative.
~ an aesthetics lover
g(x) = (x − 3)2 − 1
h(x) >
x y
−2 3
−1 −2
0 −5
1 −6
2 −5
3 −2
4 3
Answer:
The smallest minimum is attained by the function:
h(x)
Step-by-step explanation:
We are asked to find which function has smallest minimum value:
We have:
We know that the minimum value of sine function is -1 and the maximum value of sine function is 1.
So, when sine function will have minimum value -1 then the function f(x) also has minimum value as -4.
( since 2×(-1)-2=-2-2= -4 )
As this function is a quadratic function and we know that:
(x-3)^2≥0 for all x.
so,
(x-3)^2-1≥ -1.
Hence, the minimum value of g(x) is -1.
h(x) =y
x y
−2 3
−1 −2
0 − 5
1 −6
2 −5
3 −2
4 3
Clearly from the table we could see that h(x) receives -6 as the minimum value.
Hence, the smallest minimum is attained by the function h(x).
1) 0,4x (5x – 6) + 7,2 = 2x (x + 0,6);
2) x (3x+2)-9 (x²-7x)=6x (10-x);
3) 12 (x³ - 2) -7x (x² − 1) = 5x³ +2x+6.
Answer:
Давайте рассмотрим каждое уравнение по очереди:
Уравнение: 0.4x(5x - 6) + 7.2 = 2x(x + 0.6)0.4x(5x−6)+7.2=2x(x+0.6)
Раскроем скобки:
2x^2 - 2.4x + 7.2 = 2x^2 + 1.2x2x
2
−2.4x+7.2=2x
2
+1.2x
Теперь выразим все в одну часть уравнения:
-2.4x + 7.2 = 1.2x−2.4x+7.2=1.2x
3.6x = 7.23.6x=7.2
x = 2x=2
Уравнение: x(3x+2) - 9(x^2 - 7x) = 6x(10 - x)x(3x+2)−9(x
2
−7x)=6x(10−x)
Раскроем скобки:
3x^2 + 2x - 9x^2 + 63x = 60x - 6x^23x
2
+2x−9x
2
+63x=60x−6x
2
Теперь выразим все в одну часть уравнения:
3x^2 - 9x^2 + 2x - 63x - 60x + 6x^2 = 03x
2
−9x
2
+2x−63x−60x+6x
2
=0
-3x^2 - 59x = 0−3x
2
−59x=0
x(-3x - 59) = 0x(−3x−59)=0
Отсюда получаем два возможных значения xx: x = 0x=0 или x = -\frac{59}{3}x=−
3
59
.
Уравнение: 12(x^3 - 2) - 7x(x^2 - 1) = 5x^3 + 2x + 612(x
3
−2)−7x(x
2
−1)=5x
3
+2x+6
Раскроем скобки:
12x^3 - 24 - 7x^3 + 7x = 5x^3 + 2x + 612x
3
−24−7x
3
+7x=5x
3
+2x+6
Теперь выразим все в одну часть уравнения:
5x^3 - 2x^3 + 7x - 2x - 24 - 6 = 05x
3
−2x
3
+7x−2x−24−6=0
3x^3 + 5x - 30 = 03x
3
+5x−30=0
Это уравнение не имеет очевидного решения, поэтому придется использовать численные методы для его решения.